Identifying Evolutionary Patterns of SMBHs Using Characteristic Variables of the Quasar AGNs of eBOSS - Martens, Sarah Katherine (Proceedings of the Wisconsin Space Conference, 2018)
We intend to investigate the redshift distribution and environmental conditions of quasar AGNs. We employ specific redshift bins within eBOSS to draw conclusions on the evolutionary path of supermassive black holes (SMBHs) and how it is dependent on environment; in addition we seek to determine the extent to which AGN feedback is responsible for heating within the intergalactic medium of galaxy groups.